Saline Solution Oral Hygiene dalam Meningkatkan Nafsu Makan Pasien Anoreksia - Dhina Widayati; Sulistyowati Ariningsih; Muhammad Taukhid (The Indonesian Journal of Health Science, 2021)
ABSTRACT Background and Aim : Anorexia can be caused by symptoms of disease or disorders / conditions in the digestive system. To overcome the problem in anorexia that is by examining the cause of decreased or loss of appetite,where the problem of discomfort in the oral cavity can be done oral hygiene with salt water rinse.Oral hygiene is an action to clean and  refresh the mouth to eat and avoid pathogenic microfloral. This research aims to determine the effect of salt solution rinses on appetite in anorexia patients at Amelia Pare Hospital. Methods : The research design used was Pre Experiment Design with one group pre-post design approach. The population in this research were all patients with anorexia who were hospitalized at Amelia Hospital. Research time was 15-29 February 2020. The sampling technique was done by accidental sampling, as many as 30 respondents. The research instrument was a questionnaire and observation sheet, the statistical test used was the Wilcoxon Signed Rank Test. Results : the identification of appetite in anorexic patients before being given the majority of salt water rinse or more than half of respondents (53.3%) was in a pretty bad criterion. While the results of the identification of appetite in anorexic patients after being given salt water rinses showed the majority or almost half of respondents (46.7%) were in pretty good criteria. Conclusion : Based on the Wilcoxon signed rank test, p value =0,001or p α  which means there is an effect of salt water  rinse on increasing appetite in anorexia patients. Where salt contains sodium chloride which is naturally osmotic which works to absorb fluids in tissues or cells and can make bases, there by increasing pH in the mouth which can limit the amount of bacterialgrowth. Besides salt also contains water moleculer that are isotonicand do not irritate mucous membranes. This research is expected to be a reference for further research in patients who experience discomfort in the oral cavity. Keywords : oral hygiene, Salt solution, Appetite, Anorexia